THE CONCEPT OF SHAPING THE CITIES OF THE FUTURE - Karabaev G.A. Карабаев Г.А. (Рroblems of engineering and professional education, 2023)
The city is an environment that has been created over millennia and has no boundaries in the development of its architectural appearance, changing with every era and time. The formation of a new approach to the construction of cities means a change in the attitude of designers to urban design and the transition to the creation of cities of the future.